The chronicles of Pantouflia : Prince Prigio, and Prince Ricardo of Pantouflia - Lang, Andrew, 1844-1912 (D.R. Godine, 1981)
Two original fairy tales, by the renowned collector of folklore, in which Prince Prigio and Prince Ricardo struggle against the forces of evil.